Menanamkan Nilai Akhlak melalui Pemahaman Dasar-dasar Pendidikan Islam - Muhammad Yusron Maulana El-Yunusi; Ananda Chumairoh; Zuhrotul Khoiroh (MODELING: Jurnal Program Studi PGMI, 2023)
Morals are actions in everyday life that reflect human nature. These actions are things that are done naturally without any particular effort. Morals in Islam have a broad meaning. Morals in Islam are not only about humans and humans but also about humans and the Creator. This study aims to describe the basic things related to the basis of Islamic education and the concept of morality in Islam. This research method uses library research. Sources of data obtained in this study based on the literature. The results of this study include (1) the basic understanding of Islamic education (2) the basic concept of morality in the Islamic view. Overall it can be seen that in this study concept in instilling moral values through understanding the basic of Islamic education.